Discordant correlation of breast adenoid cystic carcinoma on imaging and pathology: A case report and literature review on surgical management. (2018) - Yan, Zhiyan; Leong, May Ying; Lim, Geok Hoon
Highlights: Adenoid cystic carcinomas (ACC) of the breast are extremely rare tumours, accounting for <0.1% of newly diagnosed breast cancer cases. ACC is a triple negative tumour but is known to have a much better prognosis as compared to its triple negative counterparts. There are no distinctive imaging characteristics for ACC. ACC can appear as a smooth round mass similar to that of a benign mass or as an irregular mass on mammogram. On ultrasound, ACC often manifested as a hypo- echoic heterogeneous mass and may have an indistinct margin. ACC is known to be a very infiltrative tumour, however big discrepancy between imaging size and histological size has not been reported. Our case highlights the need for judicious use of better imaging modalities to more accurately predict histological size. Abstract: Introduction: Adenoid cystic carcinomas (ACC) of the breast are extremely rare tumours, accounting for <0.1% of newly diagnosed breast cancer cases. Little data exist regarding the correlation of radiological findings with histology of this rare subtype. To our knowledge, gross size discrepancy between the 2 modalities has not been reported. We describe a case of ACC with appreciable size discordance between imaging and pathology report. Presentation of case: A 71 years old lady presented with a painless right breast lump of a few months duration. Clinical examination revealed a 1.5 cm right breast upper outer quadrant mass. Axillary and systemic examinations were unremarkable. Mammogram showed an asymmetric density in the right upper outer quadrant which corresponded to a suspicious nodule measuring about 2 cm on the ultrasound. Ultrasound of the axilla showed an indeterminate right lymph node. Core needle biopsy of the right breast nodule showed ACC while the lymph node biopsy was non- metastatic. Staging scans did not reveal any definite distant metastasis. Her naso-endoscopy and MRI of the neck were normal. She underwent a right mastectomy and sentinel lymph node biopsy. Final histology returned as a grade II 55 mm ACC. Lympho-vascular invasion was absent. The tumour was triple negative for Estrogen receptor (ER), Progesterone receptor (PR) and Human epidermal receptor 2 (HER 2). Sentinel lymph node biopsy was negative for metastasis. She recovered well but declined adjuvant chemotherapy and radiation therapy. She is currently well 6 months post operation. Discussion: ACC is an extremely rare subtype, therefore there are limited reports in literature on its imaging and pathological characteristics. Of this sparse data, there was no mention that there might be a big size discrepancy between the 2 modalities. This appreciable discrepancy has implications for pre-operative planning and the choice of breast surgery. It will be useful if the pathological extent of ACC could be determined more accurately radiologically. However, there are no distinctive imaging characteristics for ACC. ACC can appear as a smooth round mass similar to that of a benign mass or as an irregular mass on mammogram. On ultrasound, ACC often manifested as a hypo- echoic heterogeneous mass with minimal vascularity on Doppler imaging and may have an indistinct margin. MRI has a higher sensitivity than mammogram and ultrasound in determining the true extent of the tumour, but there remains little data on its usefulness in ACC. Conclusion: ACC can be extensively infiltrative and present much larger than its radiological size, as reported in our case. Use of better imaging modalities judiciously, in these cases, are needed to more accurately predict the true pathological size of ACC to prevent inadequate surgery.